(untitled) - Hannagan, Tim (Edinburgh Gate, 2005)
This contributed text examines today's most important management issues, including managerial decision making and finance with thorough exploration and analysis of key concepts and practices. It's companion web site includes, an Instructor's Manual, PowerPoint slides, and a supplementary download site with useful weblinks. Suitable for students studying business or management in further or higher education and introductory management modules for non-specialists.
Keywords: Management